Rubrivivax gelatinosus na alimentação de tilápias para incrementar a qualidade dos filés - Espirito Santo, Edson Francisco do [UNESP] (2014)
More than having productivity advantages, tilapia fish yields products with great market acceptance. For its nutrition, additives aiming at increasing zootechnical, pigmenting or antioxidant features may be used. This study evaluated the effect of the supplementation of tilapia diets with Rubrivivax gelatinosus biomass on the performance and hematological and histological parameters of the animals, and on the quality of the fillets. The experiment comprised six treatments, made of a control group, a group containing commercial pigment and four groups with biomass concentrations of 175, 350, 700 and 1400 mg/kg. Fishes weighing 21.42 ± 5.65 g were reared for 74 days in a system with water recirculation and slaughtered at days 0, 18, 43 and 74. No difference was detected for performance, histological and hematological analyzes among treatments. Fillets of the groups fed additives had lower moisture than the control (p < 0.05) while the fillets of the groups fed the biomass had the highest protein percentages (p < 0.05). No differences were detected among treatments for pH, lipids and ash values. Regarding to the color of the fillets, all treatments with additives increased redness at the measured sites (p < 0.05). For all treatments, rancidity in the fillets increased during storage, although the groups treated with the highest biomass concentrations had the lowest values (p < 0.05). R. gelatinosus biomass did not change performance or hematological and histological parameters, and proved to be capable of improving fillets quality features and conservation. Thus, it was shown the viability of the use of this additive in tilapia feed to increase the preservation of frozen meat